Detecção de Padrões Homogêneos de Vento. Parte 2: Análise de Agrupamento - Silva, Pollyanna Kelly de Oliveira; Aragão, Maria Regina da Silva; Correia, Magaly de Fatima; Silva, Alexsandra Barbosa; Santos, Samira de Azevedo (Ciência e Natura, 2011)
.